Micro-Strategy and Strategising: Introduction to the Special Issue - Whittington, R; Johnson, G; Melin, L (2003)
This introductory paper provides a background to the origins, themes and papers of this Special Issue on Micro Strategy and Strategizing. Our overarching argument is that, while the field of strategy has traditionally concentrated on the macro-level of organizations, it needs now to attend to much more micro-level phenomena. We propose an activity-based view of strategy that focuses on the detailed processes and practices which constitute the day-to-day activities of organizational life and which relate to strategic outcomes. The paper develops this view by considering two bodies of theory, those of the resource based view and institutionalism; two bodies of empirical work, those on corporate diversification and structure; and finally the process tradition of strategy research. The paper identifies the benefits of the activity-based view and introduces some challenges for further research. It concludes by introducing the papers in this Special Issue.